Maskless inverted pyramid texturization of silicon - Wang, Yan (Sci Rep, 2015)
We discovered a technical solution of such outstanding importance that it can trigger new approaches in silicon wet etching processing and, in particular, photovoltaic cell manufacturing. The so called inverted pyramid arrays, outperforming conventional pyramid textures and black silicon because of their superior light-trapping and structure characteristics, can currently only be achieved using more complex techniques involving lithography, laser processing, etc. Importantly, our data demonstrate a feasibility of inverted pyramidal texturization of silicon by maskless Cu-nanoparticles assisted etching in Cu(NO(3))(2) / HF / H(2)O(2) / H(2)O solutions and as such may have significant impacts on communities of fellow researchers and industrialists.